МОЖЛИВІСТЬ ПОТРІЙНОЇ ДЕТОНАЦІЇ В БІЛИХ КАРЛИКАХ - Дойков, Д. М.; Ющенко, О. В. (Одеські астрономічні публікації, 2021)
The induced γ-ray emissions are considered in contact cataclysmic binary systems with strong magnetic fields near white dwarfs and companion’s stars’ components. He-C-O atoms in white dwarf’s atmospheres collide with flows falling to poles as a magnetic column. Near white dwarf’s surface the falling flows with speed reaches 3 ∙ 10 6 m /s and creates sufficient conditions for nuclear γ-radiation emission. The cross sections of nuclear γ-radiation emission are presented in 0.1 – 150 MeV energy intervals depending on the colliding atoms and particles. The mass loss from binary components is of the order of ̇ ≈ (10 −11 − 10 −7 )Msun. We considered the collisions of p – He, α – He, p – C, α – C, p – N, α – N, p – O, α – O, C – He, C – C, C – N, C – O, N – He, N – C, N – N, N – O, O – He, O – C, O – N, and O – O types. Monochromatic energy luminosities Lγ in the above energy intervals for different modes in cataclysmic systems were calculated taking into account the loss of mass M , chemical composition and dynamics of fluxes incident on the magnetic poles. We found the dependencies between Lγ and chemical composition and calibrated the synthetic γ-spectra in the above pointed energy intervals. It has been concluded that power flyers are detected from p-p detonation in surface layers in white dwarf’s atmospheres. From calculation we estimated that p-p detonation time scale is in frame of the 0.07-0.1 sec. From which it is concluded that in some surface p-p explosions in the column of the magnetic field are produce significant number of positrons who has a sufficient probability to inject beyond the atmosphere of a white dwarf. It has been shown that the induce γ-ray spectroscopy together with positron spectroscopy are opens new possibilities for diagnostics of the flayers in AM Her polar system. The mechanism of triple detonation, which leads to the explosion of type I supernovae, is proposed. In this context, it is assumed that SN I type explosions occur in white dwarfs with masses not reaching the Chandrasekhar limit. The neutron formation in the matter that are in an explosive state after p-p detonation is considered separately.